Trends in Polypharmacy Among Patients with Atrial Fibrillation – A report from the Finnish AntiCoagulation in Atrial Fibrillation (FinACAF) Nationwide Cohort Study - Kiuru, Niklas (My University, 2026)
Atrial fibrillation (AF) is the most common long-standing arrhythmia, and its prevalence increases with aging of the population. Patients with AF frequently have multiple comorbidities, which predisposes them to polypharmacy, which is commonly defined as the concurrent use of five or more medications. Polypharmacy has been associated with an increased risk of adverse outcomes; however, population-level data on its prevalence and temporal trends among patients with AF have been limited. The aim of this study was to assess the prevalence of polypharmacy, associated factors, and temporal trends among Finnish AF patients between 2007 and 2018. This study was based on the FinACAF registry cohort, which included all patients diagnosed with AF in Finland during the study period. The study population comprised 229,565 patients with a newly diagnosed AF. Medication data were retrieved from national healthcare and prescription registers over a 120-day period before and after the AF diagnosis. Medications were classified according to the Anatomical Therapeutic Chemical (ATC) classification system. Following AF diagnosis, the mean number of medications used per patient was 6.0. After diagnosis, 63.1% of patients used five or more medications, and 17.7% used ten or more medications. In temporal analyses, the mean number of medications after AF diagnosis increased from 5.5 to 6.2 during study period. Medication use increased across all subgroups regardless of age, sex, prior stroke, or stroke risk scores. These findings underscore the need for holistic, patient-centered management strategies to optimize outcomes in this multimorbid population.

Eteisvärinä on yleisin pitkäkestoinen rytmihäiriö, ja sen esiintyvyys kasvaa väestön ikääntyessä. Eteisvärinäpotilailla on usein muita liitännäissairauksia, jotka altistavat monilääkitykselle eli viiden tai useamman lääkkeen samanaikaiselle käytölle. Monilääkitykseen liittyy lisääntynyt haittatapahtumien riski, mutta sen yleisyydestä ja ajallisesta kehityksestä eteisvärinäpotilailla on ollut rajallisesti saatavilla väestötason tietoa. Tämän työn tavoitteena oli selvittää monilääkityksen yleisyys, siihen liittyvät muut tekijät sekä ajalliset muutokset suomalaisten eteisvärinäpotilaiden keskuudessa vuosina 2007–2018. Tutkimus perustui FinACAF-rekisterikohorttiin, joka kattoi kaikki Suomessa diagnosoidut eteisvärinäpotilaat vuosilta 2007–2018. Aineistoon sisältyi 229 565 uutta eteisvärinädiagnoosin saanutta potilasta. Lääkkeiden käyttöä tarkasteltiin kansallisen terveydenhuollon ja reseptirekisterien tietojen perusteella 120 päivän ajanjaksolla ennen ja jälkeen diagnoosin. Lääkkeet luokiteltiin ATC-järjestelmän mukaisesti. Eteisvärinädiagnoosin jälkeen potilaiden käyttämien lääkkeiden määrä oli keskimäärin 6.0. Diagnoosin jälkeen 63.1% potilaista käytti vähintään viittä lääkettä ja 17.7% kymmentä tai useampaa lääkettä. Ajallisessa tarkastelussa käytettyjen lääkkeiden määrä eteisvärinädiagnoosin jälkeen nousi tutkimusjakson aikana 5.5:stä 6.2:een. Lääkkeiden käyttö lisääntyi kaikissa ryhmissä riippumatta iästä, sukupuolesta, aikaisemmasta aivohalvauksesta tai aivohalvausriskipisteistä. Tulokset osoittavat, että monilääkitys on merkittävä ja yleistyvä ilmiö eteisvärinäpotilailla, mikä korostaa kokonaisvaltaisen ja potilaskeskeisen hoidon merkitystä.
Keywords: atrial fibrillation, polypharmacy, comorbidity.